Tongue body position differences in the coronal stop consonants of Wubuy - Kroos, Christian; Bundgaard-Nielsen, R.; Goldstein, L.; Best, C. (Australasian Speech Science and Technology Association (ASSTA), 2010)
We investigated the role of the posterior tongue body in the articulation of the four-way coronal stop consonant series of the Australian language Wubuy. Significant tongue body posture differences between the dental, alveolar, retroflex and alveo-palatal stops were found. Further analysis revealed that the differences along the anterior-posterior axis were of the same magnitude as the difference between context vowel tongue back position and consonant midpoint position. Vowel tongue back position in the anterior-posterior dimension was predicted with a higher than expected accuracy by the consonant midpoint position, indicating a strong impact of the consonant on the vowel in Wubuy.